2019
DOI: 10.3389/fmicb.2019.00347
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Diversity Within Sediments from Two Geographically Separated Hadal Trenches

Abstract: Hadal ocean sediments, found at sites deeper than 6,000 m water depth, are thought to contain microbial communities distinct from those at shallower depths due to high hydrostatic pressures and higher abundances of organic matter. These communities may also differ from one other as a result of geographical isolation. Here we compare microbial community composition in surficial sediments of two hadal environments—the Mariana and Kermadec trenches—to evaluate microbial biogeography at hadal depths. Sediment micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
91
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(113 citation statements)
references
References 90 publications
16
91
3
3
Order By: Relevance
“…Conversely, Proteobacteria and Thaumarchaeota dominated in shallower sections. These trends are similar to previous studies [20, 21, 48, 5456]. and likely depend on the concentrations of dissolved oxygen and nitrate in sediments.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Conversely, Proteobacteria and Thaumarchaeota dominated in shallower sections. These trends are similar to previous studies [20, 21, 48, 5456]. and likely depend on the concentrations of dissolved oxygen and nitrate in sediments.…”
Section: Resultssupporting
confidence: 91%
“…S8). In general, the dominant phyla were similar to those of previous studies of abyssal and hadal sediments [20, 21, 48, 5456].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…S10). In general, the dominant phyla were similar to those of previous studies of abyssal and hadal sediments [20,21,52,57,[62][63][64]. The most abundant OTU within Eukarya belonged to Alveolata (41.5%), followed by Stramenopiles (21.0%), Nucletmycea (19.4%), Holozoa (11.7%), and Rhizaria (2.2%).…”
Section: Taxonomic Composition Of Microbial Communities In Sediment Ssupporting
confidence: 83%
“…Therefore, the labile organic carbon deposition in hadal zone supported by the high sedimentation is considered to facilitate establishment of distinct faunal and prokaryotic community observed at global scales [15][16][17][18][19]. Recently, the influence of physicochemical features on hadal biospheres were reported for microbial communities in the Mariana and Kermadec Trench regions [20,21], where under oligotrophic and relatively eutrophic (intermediate) ocean, respectively [22,23]; the pioneering studies reported microbial biodiversity in hadal trench bottom, trench slope, and adjusted abyssal plain sediments using culture-independent highthroughput sequencing techniques, and consequently demonstrated the structural similarity among each abyssal and hadal site. However, relations between geochemistry and microbial composition in hadal trench bottom and adjacent abyssal sediments have been still uninvestigated.…”
Section: Introductionmentioning
confidence: 99%